2013
DOI: 10.1038/srep01685
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline, a microglial inhibitor, reduces ‘honey trap’ risk in human economic exchange

Abstract: Recently, minocycline, a tetracycline antibiotic, has been reported to improve symptoms of psychiatric disorders and to facilitate sober decision-making in healthy human subjects. Here we show that minocycline also reduces the risk of the ‘honey trap’ during an economic exchange. Males tend to cooperate with physically attractive females without careful evaluation of their trustworthiness, resulting in betrayal by the female. In this experiment, healthy male participants made risky choices (whether or not to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Minocycline has neuroprotective qualities in animal models of neurodegenerative diseases and has been evaluated in clinical trials for a number of neurodegenerative or autoimmune diseases which affect the CNS, including stroke, Parkinson's disease, Huntington's disease, and multiple sclerosis242550. These neuroprotective activities of minocycline have been attributed to its inhibitory effects on microglial activation4751. This study indicated that microglial M1 suppressors such as minocycline could have potential benefit for behaviors and neurogenesis of offspring whose mothers experienced sleep deprivation during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline has neuroprotective qualities in animal models of neurodegenerative diseases and has been evaluated in clinical trials for a number of neurodegenerative or autoimmune diseases which affect the CNS, including stroke, Parkinson's disease, Huntington's disease, and multiple sclerosis242550. These neuroprotective activities of minocycline have been attributed to its inhibitory effects on microglial activation4751. This study indicated that microglial M1 suppressors such as minocycline could have potential benefit for behaviors and neurogenesis of offspring whose mothers experienced sleep deprivation during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal brain, the corresponding activity of minocycline modulates human social behavior leading to a more situation-oriented decision-making, possibly by suppressing the effects of personality traits (Kato et al, 2012). Minocycline also significantly reduces the risky trusting behavior in human economic exchange (Watabe et al, 2013). …”
Section: Tetracyclinesmentioning
confidence: 99%
“…In our experiment, young healthy male participants made risky choices (whether or not to trust female partners, identified only by photograph, who had decided in advance to exploit the male participants). The results show that trusting behavior in male participants significantly increased in relation to the perceived attractiveness of the female partner, but attractiveness did not impact trusting behavior in the minocycline group (61). These novel effects of minocycline may highlight the unknown roles microglia play in deeper human mental activities; microglia may modulate our unconscious drives in various social settings.…”
Section: Possible Glial Roles In Human Mental Functionsmentioning
confidence: 88%
“…As the first step to clarify this unexplored field, we have started to conduct a series of social decision-making experiments with healthy human subjects using minocycline, a microglial inhibitor (5961). Healthy Japanese adult males made a monetary decision about whether or not to trust an anonymous partner after a 4-day oral administration of minocycline.…”
Section: Possible Glial Roles In Human Mental Functionsmentioning
confidence: 99%
See 1 more Smart Citation